(untitled) (Bangladesh Pharmaceutical Journal, 2018)
Crude plant parts used as a source of medicine is an ancient practice and important for health care system worldwide. In Bangladesh, a large number of population depends on the traditional medicine using crude drugs. In traditional systems, street sellers collect powered plant parts or dried plant parts from whole sale markets locally or from various parts of Bangladesh. Favorable environmental condition for microbial growth and handling with unhygienic conditions may result in microbial contamination. The present study was performed to assess the total bacterial count and presence of coliform bacteria from 33 powdered plant part samples collected from street markets, Dhaka. Bacterial count was performed using pour plate technique in nutrient agar according to microbiological standard USP method. Bacterial growth was done by streak plate technique on MacConkey and EMB agar plates. Results showed that, 13 out of 33 samples exceeded permissible limit of bacterial count (>105 cfu/gm). However, 20 samples showed bacterial count ranging from 3.1×102 to 2×103 cfu/gm. About 48.5% samples contained Escherichia coli indicating the presence of coliform bacteria and 21.2% samples contained other enteric bacteria (unidentified) which was confirmed by bacterial growth on MacConkey and EMB agar plates. Therefore, from this study, it may be concluded that crude herbal products contain a high level of bacteria that may be associated with health risk. Bangladesh Pharmaceutical Journal 21(2): 96-100, 2018